Sosialisasi Pembuatan Kompos sebagai Upaya Menanggulangi Sampah Organik di Desa Sirnagalih - Amelia Paramitha Mahanani; Nur Paisah Pasaribu; Wahyu Purwakusuma (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Sirnagalih Village is a village that has undergone urbanization with a large number of population that generates a lot of garbage from every household, both organic and non-organic waste. One of the organic waste that is not utilized by the community is the remaining taro plants. Taro can be processed into compost that can fertilize plants. But unfortunately not many people are aware of the importance of using organic waste to be made more useful. This has led to the implementation of community assistance programs, namely socialization and composting. The purpose of this socialization and composting facilitation assistance is to increase public awareness in utilizing organic waste based on waste problems that occur in Sirnagalih Village. The method used is by interviewing the public about issues related to waste, socializing waste segregation, and making compost with the community. The result of this socialization is that farmers can process taro into compost and increase farmers' awareness of the importance of utilizing waste, especially organic waste so that it can benefit the plants again. The development of composting skills from other organic waste needs to be carried out independently by the community. In this regard, various parties including Bappeda, village government, institutions, and village government can work together well so that community service activities can run well and can develop the potential of local villages. Keywords: compost, leftover taro harvest, organic waste, utilization